Islamic Finance in the Globalized World with Special Reference to Equity Over Debt Financing - Bilal Ahmad Ganaie (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Islamic finance industry has significantly established itself in the global financial landscape since the latter half of the 20th century. Its constant substantial growth has surprised even those, not assured of its success earlier. In the economic recession of 2008, Islamic finance was termed as a safe, ethical, and vibrant alternative to the conventional financial system. In 2023, the global financial landscape faced several tough challenges characterized by geopolitical tensions, inflation and excessive debt. Despite these high challenges, the Islamic Financial Service Industry has continuously demonstrated remarkable growth. Approximately, 3.38trillion dollars of the United States is estimated to be engaged in this experiment. It has garnered attention from top global financial institutions like the International Monetary Fund, World Bank, and many other reputed financial institutions and it has equally received warm attention from global academic centers like Harvard University, Rice University, London School of Economics, and many other top universities of the world. It is currently operational in more than 75 countries via 550 Islamic financial institutions. Emerging concepts in conventional economics, such as green funds and ethical financing, constitute fundamental elements inherent in the Islamic financial system, which has consequently expanded the scope of the Islamic financial industry. Therefore, the present study explores the scope and viability of Islamic finance in the context of globalization, emphasizing equity financing as a preferable alternative to debt financing. It takes into account, how Islamic financing can help developed and developing countries to build a new world order that would be based on tranquility, cooperation, mutual help, sharing, and caring by relying more on equity financing than on debt financing. The present study discusses the repercussions of interest based debt on global economy and the need of Islamic finance to bloom economies of developed and developing countries at global level by avoiding channels of exploitative practices like interest, debt-trap, in-equality of wealth, etc. which eventually leads nations into poverty, debt, abject hunger, and un-employment. The study also examines why the debt relief packages provided to under-developing countries by developed nations have not successfully helped to address the issues of debt trap and in equality of wealth. Furthermore, the study reviews, whether Islamic finance exclusively serves the interests of Muslims only or benefits the whole humanity without any discrimination of caste creed, color, region and religion.